Prion-like low-complexity sequences: Key regulators of protein solubility and phase behavior - Franzmann, Titus M. (J Biol Chem, 2019)
Many proteins, such as RNA-binding proteins, have complex folding landscapes. How cells maintain the solubility and folding state of such proteins, particularly under stress conditions, is largely unknown. Here, we argue that prion-like low-complexity regions (LCRs) are key regulators of protein solubility and folding. We discuss emerging evidence that prion-like LCRs are not, as commonly thought, autonomous aggregation modules that adopt amyloid-like conformations, but protein-specific sequences with chaperone-like functions. On the basis of recent findings, we propose that prion-like LCRs have evolved to regulate protein phase behavior and to protect proteins against proteotoxic damage.